Diagnosis And Approaches To Treatment Of Patients Of All Ages With Simultaneous Presentation Of Ent And Cardiovascular Pathologies And Neonatal Conditions - Dzhimgirov, Mergen Ayukaevich; Koblov, Danila Yaroslavovich; Zaremba, Agneshka Andreevna; Gadzhalieva, Aitadzh Rasim kızı; Anzorova, Elizaveta Ruslanovna; Solomatina, Alexandra Mikhailovna (Journal of Neonatal Surgery, 2025)
Modern medical practice increasingly encounters clinical cases where patients exhibit symptoms affecting multiple body systems simultaneously. A special risk group includes patients presenting complaints related to a combination of ENT (ear, nose, throat) pathologies, cardiovascular dysfunction, and neonatal conditions. These cases require not only high professional expertise from treating physicians but also coordinated efforts across multiple specialties—from neonatology to cardiothoracic surgery. The presence of overlapping symptoms (e.g., dyspnea, cyanosis, reduced general tone, breathing disturbances) can complicate accurate diagnosis, especially when dealing with newborns or young children who are unable to clearly articulate their sensations. Moreover, interrelated pathologies may mask each other, increasing the risk of diagnostic errors and inappropriate therapy selection. This issue is relevant both for congenital developmental anomalies (such as nasopharyngeal hypoplasia combined with cardiac defects) and acquired conditions that complicate chronic disease progression. This paper presents modern approaches to the comprehensive diagnosis of such conditions. Special attention is given to instrumental and laboratory diagnostic methods—from endoscopic evaluation of ENT pathologies to echocardiography and duplex vascular scanning. Functional testing methods (ECG, spirometry, pulse oximetry) and their interpretation across different age groups are also discussed. The influence of congenital and acquired factors on the development of combined pathologies is analyzed, including genetic syndromes, intrauterine infections, immunodeficiency states, and environmental exposures. Clinical case examples are presented to demonstrate the effectiveness of a multidisciplinary approach in real-world settings. In the treatment section, algorithms for selecting therapeutic strategies based on patient age, severity of condition, and prognosis are reviewed. Conservative treatment options, indications for surgical intervention, rehabilitation, and postoperative monitoring are described. Particular emphasis is placed on safety and minimizing risks when treating newborns and infants within the first year of life.